An improved version of the Generalized geometric triangulation algorithm - Esteves, João Sena (2006)
Triangulation with active beacons is widely used in the absolute localization of mobile robots. The original Generalized Geometric Triangulation algorithm suffers only from the restrictions that are common to all algorithms that perform self-localization through triangulation. But it is unable to compute position and orientation when the robot is over the segment of the line that goes by beacons 1 and 2 whose origin is beacon 1 and does not contain beacon 2. This paper presents an improved version of the algorithm that allows self-localization even when the robot is over that line segment.